Impairment of central language processing in critically ill coronavirus disease 2019 patients with delirium. Issue 2 (25th March 2023) - Ferré, Fabrice; Buffières, William; Heine, Lizette; Riu, Beatrice; Curot, Jonathan; Corneyllie, Alexandra; Sarton, Benjamine; Perrin, Fabien; Silva, Stein
Abstract: Accumulating evidence indicates that coronavirus disease 2019 is a major cause of delirium. Given the global dimension of the current pandemic and the fact that delirium is a strong predictor of cognitive decline for critically ill patients, this raises concerns regarding the neurological cost of coronavirus disease 2019. Currently, there is a major knowledge gap related to the covert yet potentially incapacitating higher-order cognitive impairment underpinning coronavirus disease 2019 related delirium. The aim of the current study was to analyse the electrophysiological signatures of language processing in coronavirus disease 2019 patients with delirium by using a specifically designed multidimensional auditory event-related potential battery to probe hierarchical cognitive processes, including self-processing (P300) and semantic/lexical priming (N400). Clinical variables and electrophysiological data were prospectively collected in controls subjects ( n = 14) and in critically ill coronavirus disease 2019 patients with ( n = 19) and without ( n = 22) delirium. The time from intensive care unit admission to first clinical sign of delirium was of 8 (3.5–20) days, and the delirium lasted for 7 (4.5–9.5) days. Overall, we have specifically identified in coronavirus disease 2019 patients with delirium, both a preservation of low-level central auditory processing (N100 and P200) and a coherent ensemble of covert higher-order cognitive dysfunctions encompassing self-related processing (P300) and sematic/lexical language priming (N400) (spatial–temporal clustering, P -cluster ≤ 0.05). We suggest that our results shed new light on the neuropsychological underpinnings of coronavirus disease 2019 related delirium, and may constitute a valuable method for patient's bedside diagnosis and monitoring in this clinically challenging setting. Abstract : Ferré et al . report covert high order cognitive dysfunctions, encompassing prediction of lexical/semantic occurrence and self-relevant auditory stimuli detection, in delirium versus non-delirium critically ill coronavirus disease 2019 patients by means of electrophysiological signatures (N400 and P300 event-related potentials). Graphical Abstract: Graphical Abstract